The development of performance measurement framework in the management of public office buildings in Malaysia - Mohd Isa, Zailan (2004)
The research is an exploratory study on operational property management. It seeks to explore the concept of performance measurement in the management of public office buildings in Kuala Lumpur. In this study, a conceptual framework based on the balanced scorecard approach is presented to explore and understand the performance measurement system in property management of operational property in the public sector. It is argued that property management have been a neglected area among practitioners particularly the public property. Hence, this research started as a result of realising the importance of efficient and effective public property management to extract the best value of public investment. In this study, there are two problems: Firstly, it is to develop a conceptual framework for performance measurement in the management of public office buildings. Secondly, it is to determine critical success factors (CSFs) and identify key performance indicators (KPIs) based on the conceptual framework. This research adopts a case study approach as the research strategy in a multiple-case design. Three public office buildings in Kuala Lumpur are identified as the case studies. It is concluded that, in general, the performance measurement system in the case studies can be categorised as mix measurable performance approach of both financial and nonfinancial performance measures. However, the findings show that the case studies ignore the importance of property objectives in monitoring properly performance and their management to achieve effective and efficient management. The approach is not well structured as a management tool and lacking in specification of critical factors to be considered as performance indicators. The study identifies 28 CSFs and their corresponding 120 KPIs within the four perspectives of financial, customer satisfaction, internal processes, and innovation and continuous improvement as laid in the balanced scorecard approach of performance measurement.